Rearranging the equation, we get:
x^2 + 4x + 3 = 0
Using the quadratic formula, where ax^2 + bx + c = 0:
x = (-b ± sqrt(b^2 - 4ac))/(2a)
In this case, a = 1, b = 4, and c = 3.
x = (-4 ± sqrt(4^2 - 4(1)(3)))/(2(1))
x = (-4 ± sqrt(16 - 12))/(2)
x = (-4 ± sqrt(4))/2
x = (-4 ± 2)/2
This gives us two possible solutions:
x = (-4 + 2)/2 = -2/2 = -1
x = (-4 - 2)/2 = -6/2 = -3
Therefore, the solutions to the equation x^2 + 3 = -4x are x = -1 and x = -3.
Use the quadratic formula to solve the equation. If necessary, round to the nearest hundredth.
x^2+3=-4x
1 answer